Ni-Co layered double hydroxide coated on microsphere nanocomposite of graphene oxide and single-walled carbon nanohorns as supercapacitor electrode material - Kim, Ji Hoon; Ko, Yong-il; Lee, Seo Yun; Lee, Yun Seon; Kim, Su Kyung; Kim, Yoong Ahm; Yang, Cheol-Min (John Wiley & Sons Inc., 2022)
Ni-Co layered double hydroxides (LDH) have received considerable attention as excellent pseudocapacitor electrode materials. In this paper, a novel utilization of the composite of graphene oxide (GO) and single-walled carbon nanohorns (SWCNHs) is reported as an effective substrate for LDH coatings. We successfully synthesized hierarchical nanostructures composed of Ni-Co LDH as well as microsphere composites of GO and oxidized SWCNHs (o-NH). A dense microsphere composite of GO and o-NH was synthesized using the spray-drying method (s-(GO/o-NH)). Subsequently, the prepared Ni-Co LDH nanosheets were directly coated on the s-(GO/o-NH) microspheres using the hydrothermal method (LDH@s-(GO/o-NH)). Moreover, the electrochemical characteristics of the LDH@s-(GO/o-NH) supercapacitor electrodes were evaluated in a 6 M KOH electrolyte. In the three-electrode system, the LDH@s-(GO/o-NH) composite electrode exhibited a significantly high gravimetric specific capacitance (1046 F g(-1) at 1 mV s(-1)) and excellent specific capacitance retention (84% retention after 10 000 cycles at 100 mV s(-1)) compared with 211 F g(-1) and 79% for the LDH@s-GO composite electrode, respectively. The supercapacitive behavior of the LDH@s-GO and LDH@s-(GO/o-NH) electrodes in the two-electrode system exhibited a trend similar to that of the three-electrode system. The superior electrochemical performance of the LDH@s-(GO/o-NH) composite electrode can be ascribed to its high electrical conductivity and pseudocapacitance, indicating that the s-(GO/o-NH) microsphere composite with an interconnected pore network structure can be utilized as a support for effectively coating Ni-Co LDH components. The LDH@s-(GO/o-NH) composite electrode is a promising candidate for pseudocapacitor applications because of its excellent electrochemical characteristics and facile synthesis, making it suitable for industrial and consumer applications.